Hegemonic masculinity and genre mediation in contemporary religious cinema: A comparative Connellian-Freirean analysis of Immaculate (2024) and Women Talking (2022) - Sirait, Ester Yoanita; Nurmansyah, Mochamad Andhy (NOTION: Journal of Linguistics, Literature, and Culture, 2026)
Debates on gender inequality in Christian contexts often focus on doctrine and sociocultural patriarchy, yet genre’s influence on these issues at the narrative level is rarely examined. This study investigates how Immaculate (2024) and Women Talking (2022) construct representations of masculinity, religious authority, and female resistance through horror and drama conventions. Using qualitative interpretive film analysis, the research involved repeated close viewing, scene logging, and iterative coding. Recurring patterns were identified inductively and examined through Raewyn Connell’s (2005) framework of power, production, and cathexis, alongside Paulo Freire’s (1970) concept of internalized oppression. The analysis indicates that biblical references within the films’ narrative worlds become aligned with feminine-coded expectations of endurance and restraint through cinematic form rather than doctrinal meaning. Spatial confinement, sound design, dialogue, and visual framing contribute to this alignment. Horror externalizes patriarchal control through spectacle, while drama organizes authority through deliberation. In both cases, resistance emerges within, rather than outside, existing structures of power. The study contributes by positioning genre as a mediating framework through which religious authority and gender hierarchy are narratively organized in these texts. Given its focus on two films, further research is recommended across broader genres, global cinemas, and media forms.